The Role of Self-compassion in Predicting Loneliness and Self-efficacy in the Elderly - Mehdi Ghezelseflo; Mozhgan Mirza (Sālmand, 2020)
Objectives: Giving the growing population of the elderly, it is important to pay attention to their psychological health. The purpose of this study was to examine the role of self-compassion in predicting loneliness and self-efficacy in the elderly. Methods & Materials: This is a descriptive correlational study. Study population consisted of all elderly residents of Gonbad Kavous County in Iran. Of these, 120 (70 women and 50 men) were selected using a convenience sampling technique. Data collection instruments were University of California, Los Angeles (UCLA) Loneliness Scale of Russell et al. (1966), General Self-efficacy Scale of Scherer et al. (1982) and Self-Compassion Scale of Neff (2003). Data analysis was performed by using Pearson correlation coefficient and multiple regression analysis. Results: Loneliness had a significant negative relationship with self-compassion dimensions of self-kindness, common humanity, mindfulness and its overall score, and a significant positive relationship with self-judgment, isolation and over-identification. Moreover, self-efficacy had a significant positive relationship with self-kindness, common humanity, mindfulness and overall self-compassion score, and a negative significant relationship with self-judgment, isolation and over-identification (P≤0.001). Self-kindness, self-judgment, common humanity, isolation, mindfulness and overall self-compassion score can predict 43% of loneliness variance and self-kindness, self-judgment, mindfulness, isolation and overall self-compassion score can predict 38% of self-efficacy variance. Conclusion: Self-compassion have an effective role in reducing loneliness and increasing self-efficacy in the elderly.